Comparative analysis of photosynthetic properties in ice algae and phytoplankton inhabiting Franklin Bay, the Canadian Arctic, with those in mesophilic diatoms during CASES 03-04 - Ban, Akiko; Aikawa, Shimpei; Hattori, Hiroshi; Sasaki, Hiroshi; Sampei, Makoto; Kudoh, Sakae; Fukuchi, Mitsuo; Satoh, Kazuhiko; Kashino, Yasuhiro (National Institute of Polar Research, 2006)
P(論文) Psychrophilic phytoplankton and ice algae were collected in Franklin Bay, the Canadian Arctic, in late May 2004, and the photosynthetic properties were measured at 4°C using a pulse amplitude modulation fluorometer (Phyto-PAM). Rapid light curve measurements allowed for the assessment of the photosynthetic efficiency (α), maximal electron transport rate (rETRmax), and minimum saturating irradiance (Ek) in the samples. The values of α in phytoplankton (0.63-0.68) were much larger than those in ice algae (0.10-0.51), and the values of rETRmax in phytoplankton (4.6-6.7) were relatively larger than those in ice algae (1.8-4.3). However, Ek showed similar values in both samples and were around 10μmol photonsm^<-2>・s^<-1>. These values were systematically compared with those obtained from mesophilic marine diatoms (a centric diatom, Chaetoceros gracilis, and a pennate diatom, Phaeodactylum tricornutum) grown under various irradiances in the laboratory. The highly shade-adapted features of ice algae and phytoplankton were disclosed through this comparative analysis. It was also found that the non-photochemical quenching was much higher in psychrophilic samples than in mesophilic diatoms grown under moderate irradiance. Furthermore, in ice algae and phytoplankton, the decrease in rETR at high irradiances was prominent, showing that they were highly susceptible to photoinhibition. Our comparative analysis using psychrophilic phytoplankton, ice algae and two strains of mesophilic diatoms also revealed that the dependency on the xanthophyll cycle for the protection mechanisms of photosystems were remarkably different between the groups, indicating that the acclimation strategies to growth irradiances were variable between species. Such variable acclimation strategies could be one of the forces that results in a diverse algal flora that enables this region around Franklin Bay to be a productive area, even though the psychrophilic phytoplankton and ice algae are highly shade-adapted. departmental ...